Mining companies and Local Economic and Social Development in the Greater Tubatse Municipal Area of Limpopo Province in South Africa - Ramphele, Samuel Motlatso (My University, 2011)
The mining sector in South Africa has enjoyed decades of profiteering and unchecked neglect of developmental needs of surrounding communities. Most of the communities surrounding South African mines are therefore synonymous with social problems that include poverty, poor health, unemployment, adult illiteracy, poor housing, family disorganization and high influx of unaccompanied migrant labour. On the contrary, mining is presented as the paradigm of wealth in particular when dealing with gold and diamond mining, while its marketing conceals its terrible social and environmental consequences. However mining is responsible for such impacts and many others. This study looks at the socio-economic impact of mining on community development in Greater Tubatse Municipal area located in Limpopo Province, South Africa. From the interviews conducted and questionnaires administered to sampled community members and workers of the platinum mine in Greater Tubatse Municipality, it emerged that the existence of mining companies in the area has done little to uplift the lives of the people in terms of socioeconomic development. The study makes recommendations on how the situation can be improved so that the population living in the area can benefit from the work carried out by mining companies.
Thesis (M.Dev.) -- University of Limpopo, 2011
Keywords: Mining companies; Local economic and social development; Community development; Mining industries -- South Africa -- Limpopo; Mineral industries; Rural development